Relation between management and leucaena (Leucaena leucocephala) to prevent its transformation into an invasive plant - Ruiz, T. E.; Alonso, J.; Valenciaga, N.; Febles, G.; Lok, S.; Galindo, J.; Díaz, H.; López, A. (Cuban Journal of Agricultural Science, 2018)
The effect of management was evaluated to prevent leucaena becoming an invasive plant. For five years, the evolution of two systems was studied: 1) tree legume Leucaena leucocephala cv. Peru in silvopastoral system, where it occupied 100 % of the area, associated with Brachiaria brizantha cv. Marandú for cattle fattening; 2) tree legume Leucaena leucocephala cv. Peru, where it occupied 100 % of the area, associated with Brachiaria brizantha cv. Marandú without being grazed. A random block design was applied, with five replications. Indicators in the leucaena-brachiaria system with animal grazing were better, at the beginning and at the end of the experiment, with a decrease in the depopulation of 1 plant/m2 (P = 0.0012), higher grass population 11.2/m2 (P = 0.0014) and low presence of weeds 1 plant/m2 (P = 0.0039), which was better in the system without grazing. Leucaena component had a different performance, according to the studied system. In the system under grazing, yield of brachiaria base grass was always superior (2.2 and 3.0 t/ha DM) with respect to the non-managed system, at the beginning (P = 0.0028) and at the end of the experimental stage. The same happened with the presence of natural grass 0.40 t/ha DM (P=0.0011), which disappeared at the end. Weeds had a higher presence in the non-managed area 0.31 t/ha DM (P = 0.0101) at the beginning of the study. It is concluded that the technological proposal for the management of systems with Leucaena leucocephala in silvopastoral systems is a functional and feasible option to apply so that this species does not become invasive. Key words: productive stability, brachiaria, invasive plant, silvopastoral system